Strategic plan for sustainable rural tourism in San Isidro and Charapotó, Manabí, Ecuador - Bayas Escudero, Johnny Patricio (2015)
This strategic plan was formulated with the objective of implementing and developing sustainable rural tourism in San Isidro and Charapotó as a new alternative of local development through the application of planning and tourism management, all of which will facilitate the appropriate use of tourism resources for improving quality of life of the local people. The plan was designed in three stages. First, we conducted a situational diagnosis based on the information obtained from the main actors in the tourism sector of Sucre and of both study communities, who indicated their main strengths and weaknesses in relation to tourism. The diagnosis was conducted using internal- external-factor evaluation matrixes. Thirteen resources were identified through the application of tourism inventory worksheets. A potentiality matrix was used to identify the degree of relevance of each inventoried tourist site. Environmental impacts of most vulnerable tourist sites were evaluated through the Leopold matrix. The SWOT analysis was used to establish plan strategies. In the second stage, we established the mission, vision, values, policies, strategic objectives, programs and projects. The time of project completion was established through a timeframe including the respective budget. The last stage dealt with evaluation parameters indicating dissemination media as well as the tools for monitoring and evaluating programs and projects.